Perempuan dan Kepemimpinan Gereja: Suatu Dialog Perspektif Hermeneutika Feminis - Bobby Kurnia Putrawan (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2020)
The feminist movement became a movement that moved and challenged the church from the comfort of male domination. The role of women is increasingly strengthened and developed in various aspects of life, including aspects of church leadership. This resulted in debates among male-dominated church leaders; whether women's leadership roles can be accepted or rejected. This article is presented to add to the theological study of women and their leadership in the church through the perspective of feminist hermeneutics while upholding respect and authority for the Bible. The method used is grammar-accommodative, which is a combination of grammatical understanding of the text and translatively translated. Finally, the involvement of women in the formation of Christian social ethics in the future will broaden the horizon of understanding the interaction of women and men in social structures and ecclesiastics. Abstrak Gerakan feminis menjadi sebuah gerakan yang menggugah dan meng-gugat gereja dari kenyamanannya dominasi laki-laki. Peranan perempuan semakin diperkuat dan dikembangkan di pelbagai aspek kehidupan, termasuk aspek kepemimpinan gereja. Hal ini ini berdampak perdebatan di kalangan pimpinan gereja yang didominasi laki-laki; apakah peranan kepemimpinan perempuan bisa diterima atau ditolak. Artikel ini disajikan untuk menambah kajian teologis mengenai perempuan dan kepemimpinannya di gereja melalui perspektif hermeneutika feminis, dengan tetap menjunjung tinggi penghargaan dan otoritas terhadap Alkitab. Metode yang digunakan adalah grammar-akomodatif, yang merupakan perpaduan pengertian teks secara gramatikal dan diterjemahkan secara akomo-datif. Akhirnya, keterlibatan perempuan ke dalam pembentukan etika sosial Kristen di masa depan akan memperluas cakrawala pemahaman tentang interaksi perempuan dan laki-laki dalam struktur sosial dan kegerejawian.